2018
DOI: 10.2147/cia.s157182
|View full text |Cite
|
Sign up to set email alerts
|

Inter-gender differences of balance indicators in persons 60–90 years of age

Abstract: IntroductionPrecision of movements responsible for maintaining balance deteriorates with age due to natural involutionary processes, thus prompting a research question whether the values of gender-related stability indicators might differ significantly among the study subjects over 60 years of age.MethodsThe study group comprised 136 seniors (89 women, 47 men; aged 60–90 years). The CQ-Stab 2P 2-platform posturograph was used as the main research device, whereas the Mann–Whitney U-test was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
3
21
0
6
Order By: Relevance
“…Opposite results were found when analyzing balance, as females showed a similar decrease in all age groups, while for males the decline was not linear with the OLDER males (≥75 years) showing larger decreases when compared to the YOUNGER males (65-69.9 years). Our results are in line with those of Puszczaloska-Lizis et al [33], who compared different balance-related variables in males and females of three different age groups (60-69 years, 70-79 years and 80-90 years). Although the researchers did not evaluate the differences between age groups within sexes, they did find that most of the statistically significant sex-related differences were observed for the 70-79 and 80 to 90 year groups (favoring the female group), which would correspond with the OLDER group of the present study, suggesting that the decline in postural stability is steeper in men than in women.…”
Section: Discussionsupporting
confidence: 93%
“…Opposite results were found when analyzing balance, as females showed a similar decrease in all age groups, while for males the decline was not linear with the OLDER males (≥75 years) showing larger decreases when compared to the YOUNGER males (65-69.9 years). Our results are in line with those of Puszczaloska-Lizis et al [33], who compared different balance-related variables in males and females of three different age groups (60-69 years, 70-79 years and 80-90 years). Although the researchers did not evaluate the differences between age groups within sexes, they did find that most of the statistically significant sex-related differences were observed for the 70-79 and 80 to 90 year groups (favoring the female group), which would correspond with the OLDER group of the present study, suggesting that the decline in postural stability is steeper in men than in women.…”
Section: Discussionsupporting
confidence: 93%
“…This is the only factor that could explain our results. Comorbidity, medication or socioeconomic differences, other important-factors mentioned in the literature as responsible for poor balance [ 29 31 ] should not be taken into account in our present work because we selected for healthy subjects, unhealthy were excluded, and they were mostly couples with a similar socioeconomic status. Nevertheless, despite the oral report of physical activity, due to the absence of a systematic collection of this information through self-reports or administered scales, we consider that one should take with caution the interpretation that the differences in balance score between genders is due to differences in levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…We want to highlight these results, which lead us to ask ourselves if better balance in independent elderly people who have no history of a recent fall is linked to gender. There is no consensus in the literature: some studies did not find them, while others observed indeed lower levels of postural stability and balance for men [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on CTSIB showed no differences between males and females [6]. Some other studies, however, have shown sex differences [14][15][16][17]. The problem of postural control and aging may be more related to the complexity of postural sway than to any single factor, however [18].…”
Section: Discussion/conclusionmentioning
confidence: 88%